A method for slowing down depletion of myocardial energy reserves of the donor heart before transplantation - Vavrínková, H; Tutterová, M; Vránová, Z; Vrána, M (Bratislavske lekarske listy, 1991)
One of the methods of donor heart protection against ischemia is a substantial lowering of temperature of the heart perfused with cardioplegic solution (CS). The achieved conservation of energetically rich compounds, however, does not guarantee the full restoration of heart function during reperfusion. Another possibility for heart preservation is repeated application of CS at 20 degrees C. This variant was tested in our experiments on isolated rat hearts perfused under constant pressure with the Krebs-Henseleit solution according to Langendorff. During global ischemia (180 min at 20 degrees C) we applied the St. Thomas Hospital CS lx or 4 x at 60 min intervals. During the ischemia, glycogen, ATP, lactate, Na+, K+ were assessed in the heart. The heart injury was monitored as the release of lactate dehydrogenase (LD) during the 60 min reperfusion. Repeated CS perfusion of the heart during ischemia lowers the contents of lactate and maintains ATP and glycogen content at elevated levels throughout ischemia. The improved condition of the heart after repeated CS application demonstrated as prevention of the gain of Na+ in the cells at the end of ischemia as well as after reperfusion. This was associated with reduced intracellular potassium depletion and LD release into the perfusate.
Keywords: energetický metabolismus; Heart Transplantation; Lactic Acid; adenosintrifosfát; Cardioplegic Solutions; laktáty; Myocardial Reperfusion; uchovávání orgánů; kardioplegické roztoky; techniky in vitro; Myocardium; Organ Preservation; transplantace srdce; Lactates; krysa rodu Rattus; glykogen; kyselina mléčná; Animals; Energy Metabolism; zvířata; Rats; Adenosine Triphosphate; Glycogen; myokard; reperfuze myokardu; In Vitro Techniques